Indian Military Modernization Under Modi's regime - Dost Muhammad Barrech; Arhama Siddiqa (BTTN Journal, 2022)
The past few decades have seen a structural shift in international politics, with multilateralism replacing bilateralism, as evidenced by China’s rise in security and economic domains. The turn of the 21st century has also seen the rise of another aspiring power- India. With the assumption of office by Prime Minister Modi in 2014, the Indian military has been going through fundamental changes. Under the ‘Joint Indian Armed Forces and the Land Warfare Doctrines’, India aims to achieve greater strategic outreach. Indian military modernization since 2014 witnessed a steep rise. India being a strategic ally of the US, has been emboldened to modernize its military that, by and large, will make New Delhi more belligerent, augmenting Pakistan’s security concerns. Though a lot has been written on India’s military modernization, this paper seeks to address the gap in the literature on how the modernization factor has come about, driven primarily by the Hindutva ideology underpinned by the Modi regime. By incorporating the neo-realistic perspective, this paper argues that unless countermeasures are taken, Indian aggression and military modernization might trigger a full-blown war in the foreseeable future especially given that Modi may come back to power in 2023.